Genome Analysis of Goose-Origin Astroviruses Causing Fatal Gout in Shanghai, China Reveals One of Them Belonging to a Novel Type Is a Recombinant Strain - Shen, Quan; Zhuang, Zi; Lu, Juan; Qian, Lingling; Li, Guangquan; Kanton, Aaron Gia; Yang, Shixing; Wang, Xiaochun; Wang, Huiying; Yin, Jun; Zhang, Wen (Frontiers in Veterinary Science, 2022)
Since 2014, goose-origin astrovirus (GAstV) disease occurred in China and rapidly spread to major commercial goose provinces, has been leading to huge economic losses in the poultry industry. In March 2020, a goose farm locates in Shanghai of China, where there was no goose astrovirus (GAstV) infection report before, experimented an outbreak of gout disease in geese. The etiological investigation was carried out by virus metagenomics and bacterial culture and two GAstV strains, designated as CHSH01 and CHSH02, were determined. The complete genomes of them were 7154 and 7330 nt in length exclude the oligo(dT) tail, respectively, and have different genomic feature and classification. CHSH01 shared very low sequence identity with other strains in terms of not only complete genome but also other genes. Phylogenetic analysis showed CHSH02 belonged to GAstV-2, which was the predominant species in the geese with gout in China according to the previous study. Meanwhile, the CHSH01 strain displayed low identity with other AstVs, and phylogenetic and recombination analysis suggested that CHSH01 formed a novel species was a recombinant strain, one parent strain of which was an AstV determined from a bar-headed goose (a kind of migrant bird). Moreover, the primary prevalence investigation showed that the two strains were prevalent in the same goose farm and co-infection occurred. These findings arise the potential cross-species transmission of CHSH01 between domestic and wild fowl.